68Ga-FAPI-04 PET-CT for molecular assessment of fibroblast activation and risk evaluation in systemic sclerosis-associated interstitial lung disease: a single-centre, pilot study. (March 2021) - Bergmann, Christina; Distler, Jörg H W; Treutlein, Christoph; Tascilar, Koray; Müller, Anna-Theresa; Atzinger, Armin; Matei, Alexandru-Emil; Knitza, Johannes; Györfi, Andrea-Hermina; Lück, Anja; Dees, Clara; Soare, Alina; et al.
Summary: Background: Interstitial lung disease (ILD) is the most common cause of death in systemic sclerosis. To date, the progression of systemic sclerosis-associated ILD is judged by the accrual of lung damage on CT and pulmonary function tests. However, diagnostic tools to assess disease activity are not available. Here, we tested the hypothesis that quantification of fibroblast activation by PET-CT using a 68 Ga-labelled selective inhibitor of prolyl endopeptidase FAP ( 68 Ga-FAPI-04) would correlate with ILD activity and disease progression in patients with systemic sclerosis-associated ILD. Methods: Between Sept 10, 2018, and April 8, 2020, 21 patients with systemic sclerosis-associated ILD confirmed by high-resolution CT (HRCT) within 12 months of inclusion and with onset of systemic sclerosis-associated ILD within 5 years or signs of progressive ILD and 21 controls without ILD were consecutively enrolled. All participants underwent 68 Ga-FAPI-04 PET-CT imaging and standard-of-care procedures, including HRCT and pulmonary function tests at baseline. Patients with systemic sclerosis-associated ILD were followed for 6 months with HRCT and pulmonary function tests. We compared baseline 68 Ga-FAPI-04 PET-CT uptake with standard diagnostic tools and predictors of ILD progression. The association of 68 Ga-FAPI-04 uptake with changes in forced vital capacity was analysed using mixed-effects models. Follow-up 68 Ga-FAPI-04 PET-CT scans were obtained in a subset of patients treated with nintedanib (follow-up between 6–10 months) to assess change over time. Findings: 68 Ga-FAPI-04 accumulated in fibrotic areas of the lungs in patients with systemic sclerosis-associated ILD compared with controls, with a median standardised uptake value (SUV) mean over the whole lung of 0·80 (IQR 0·60–2·10) in the systemic sclerosis-ILD group and 0·50 (0·40–0·50) in the control group (p<0·0001) and a mean whole lung maximal SUV of 4·40 (range 3·05–5·20) in the systemic sclerosis-ILD group compared with 0·70 (0·65–0·70) in the control group (p<0·0001). Whole-lung FAPI metabolic active volume (wlFAPI-MAV) and whole-lung total lesion FAPI (wlTL-FAPI) were not measurable in control participants, because no 68 Ga-FAPI-04 uptake above background level was observed. In the systemic sclerosis-ILD group the median wlFAPI-MAV was 254·00 cm 3 (IQR 163·40–442·30), and the median wlTL-FAPI was 183·60 cm 3 (98·04–960·70). 68 Ga-FAPI-04 uptake was higher in patients with extensive disease, with previous ILD progression, or high EUSTAR activity scores than in those with with limited disease, previously stable ILD, or low EUSTAR activity scores. Increased 68 Ga-FAPI-04 uptake at baseline was associated with progression of ILD independently of extent of involvement on HRCT scan and the forced vital capacity at baseline. In consecutive 68 Ga-FAPI-04 PET-CTs, changes in 68 Ga-FAPI-04 uptake was concordant with the observed response to the fibroblast-targeting antifibrotic drug nintedanib. Interpretation: Our study presents the first in-human evidence that fibroblast activation correlates with fibrotic activity and disease progression in the lungs of patients with systemic sclerosis-associated ILD and that 68 Ga-FAPI-04 PET-CT might improve risk assessment of systemic sclerosis-associated ILD. Funding: German Research Foundation, Erlangen Anschubs-und Nachwuchsfinanzierung, Interdisziplinäres Zentrum für Klinische Forschung Erlangen, Bundesministerium für Bildung und Forschung, Deutsche Stiftung Systemische Sklerose, Wilhelm-Sander-Foundation, Else-Kröner-Fresenius-Foundation, European Research Council, Ernst-Jung-Foundation, and Clinician Scientist Program Erlangen.